A Normative Analysis of the Regulation of Termination of Employment For Fixed-Term Employment Agreements Workers Following the Job Creation Law: Kajian Normatif Pengaturan Pemutusan Hubungan Kerja Pekerja Perjanjian Kerja Waktu Tertentu Pasca Undang-Undang Cipta Kerja - Grace Natalie Lim; Gunardi Lie (Academia Open, 2025)
General Background: The regulation of termination of employment for workers under Fixed-Term Employment Agreements (PKWT) has gained urgency following recent reforms in Indonesia’s labor market. Specific Background: The Job Creation Law and Government Regulation No. 35/2021 introduced new standards intended to enhance flexibility while reshaping the protection framework for contract workers. Knowledge Gap: Despite these reforms, inconsistencies in interpretation, weak enforcement, and uneven implementation continue to create legal uncertainty, particularly in cases of unilateral termination and compensation. Aims: This study conducts a normative juridical analysis to assess the alignment of PKWT termination regulations with core principles of national labor law. Results: The findings indicate that although the new regulations clarify compensation entitlements, they do not fully guarantee fairness or legal certainty due to limited worker awareness, regulatory overlap, and ineffective supervisory mechanisms. Novelty: This research offers an integrated assessment that connects statutory reform, judicial practice, and labor protection principles, exposing gaps between legal norms and practical application. Implications: Enhanced harmonization, stronger supervisory systems, and clearer technical regulations are necessary to achieve balanced labor flexibility and social justice within Indonesia’s evolving industrial relations framework. Highlights: Highlights legal changes to PKWT termination and compensation after the Job Creation Law. Reveals gaps between normative protection and practical implementation in the field. Emphasizes the need for harmonized regulations and stronger labor supervision. Keywords: Fixed-term Employment Agreements, Termination of Employment, Job Creation Law, Worker Protection, Labor Law Reform